Surface characterization of silicon nitride powder and electrokinetic behavior of its aqueous suspension. Issue 7 (May 2020) - Ni, Zhentao; Jiang, Jie; Yang, Xianfeng; Yang, Xiaole; Zhou, Zhe; He, Qinglong
Abstract: The dispersion stability of aqueous suspensions containing silicon nitride nanopowder prepared by direct nitridation had been studied. The Si3 N4 powder was calcined at 200 °C, 400 °C and 600 °C, respectively. It was aimed to improve dispersion stability of Si3 N4 suspension, and the effects were evaluated by measuring the median diameters of the samples taken from the slurries after settling experiments. The relationship between the median diameter and the viscosity of the slurry was discussed on the basis of Stoke's law. High resolution transmission electron microscopy (HRTEM) clearly revealed that the calcined Si3 N4 particles were covered by an amorphous surface layer, which was mainly composed of silica. It can also be easily verified according to the results of X-ray photoelectron spectroscopy (XPS) analyses and diffuse reflectance Fourier transform infrared spectroscopy (DRTIFT) measurements. The formation of oxide layer also led to an increase in the total oxygen content of Si3 N4 powder. Inductively coupled plasma atomic emission spectrometry (ICP-OES) analyses showed that the soluble impurities decreased after thermal oxide process, which also contributed to the lower of viscosity according to Jones-Dole expression. Electrokinetic behavior of suspensions also indicated that the absolute value of ζ-potential increased after powder calcination.